AN ANALYSIS OF THE EXPRESSIVE SPEECH ACTS USED BY JOHN AND SAVANNAH AS THE MAIN CHARACTERS IN DEAR JOHN MOVIE - Novy Widyowati (Universitas Sarjanawiyata Tamansiswa, 2019)
The purposes of this research are 1) to identify the types of expressive speech acts used by the main characters of Dear John movie and 2) to find out the function of the expressive speech acts used.The type of this research is discourse analysis mixed with quantitative method to explain the data further. The data of the research was taken fromÂ Dear John movie. The instruments of this research were the utterances from the main characters of Dear John movie which categorized and put into observation table. The data were analyzed based on the theories of Yule (1996) and Clark (1995) of expressive speech acts to answer the research questions. The results of this research showed that the expressive speech act used by the main characters of Dear John movie consisted of 6 types out of 7 types. They are the expression of pleasure, liking, disliking thanking, apologizing, and the expression of praise. The type of speech act that was not found in the utterances of the main character was congratulating. The most dominant type that was found in the utterances of the main character wasÂ thanking.